Biclique cryptanalysis of the full‐round KLEIN block cipher. Issue 5 (1st September 2015) - Ahmadian, Zahra; Salmasizadeh, Mahmoud; Aref, Mohammad Reza
Abstract : In this study, the authors evaluate the security of the lightweight block cipher KLEIN‐64 using biclique cryptanalysis. They first point out some new weaknesses of the diffusion layer and key schedule of this algorithm. Then they exploit them to cryptanalyst the full round version of KLEIN‐64 using an asymmetric biclique. The (worst case) computations and data complexity of this cryptanalysis are 2 62.84 and 2 39, respectively. A modified version of this cryptanalysis is also presented which is slightly faster at the expense of the data required.